Decellularized Mouse Liver as a Small-Scale Scaffold for the Creation of a Miniaturized Human Liver - Hiroyuki Ijima; Yukako Fukuda; Mario Kokichi Uehara; Muhammad Shafiq; Fanqi Wu; Jaeyong Cho; Yusuke Sakai; Tatsunori Miyata; Takanobu Yamao; Yosuke Nakao; Yosuke Kuroda; Takashi Motomura; et al. (Journal of Chemical Engineering of Japan, 2023)
The liver is the main organ responsible for drug metabolism; hepatocyte-based culture models play a fundamental role in understanding liver physiology. While different types of two-dimensional and three-dimensional liver models have been developed, the failure to accurately mimic native liver, including extracellular matrix (ECM) composition, complex structure, and rich vascular network as well as shortage of liver donors, impede their clinical translation. Herein, we have realized a “miniature human liver” based on the infusion of primary human hepatocytes into a decellularized liver template (DC-liver) made from the right liver lobe of mouse. We performed detergent-based decellularization of the mouse liver sections via portal vein (PV) perfusion and confirmed the successful removal of cell content, and the preservation of the vascular network. Subsequently, the DC-liver templates were recellularized at varying cell densities, including 3 × 106 and 1 × 107 cells/mL, and liver specific gene expression was assessed. Overall, hepatocytes in the recellularized liver constructs (RC-liver) expressed liver-specific mRNA expression markers (Hnf4α, Alb) at a level comparable to the unseeded, freshly isolated hepatocytes and to hepatocytes seeded inside collagen gels. However, the RC-liver with the highest cell density exhibited poor cell distribution and blockage of the PV, in general, hepatocytes showed elevated levels of Cyp1a1. Further analysis hinted at hypoxic conditions inside the constructs, showing higher mRNA expression levels of hypoxia-related genes (Hif-1α, Casp3, Zo-1). Fortunately, oxygen supplementation appeared to alleviate hypoxia, which markedly reduced expression levels of Hif-1α and Cyp1α1. As a proof-of-concept, primary human hepatocytes were also seeded into the DC-liver templates, and we could confirm liver specific mRNA expression (HNF4A, ALB, CYP3A4). Altogether, the above results indicate a profound potential in the use of DC-liver tissue for the fabrication of a miniature human liver, which may have potential application prospects for regenerative medicine, tissue engineering (TE) and other related disciplines.